Seismic vulnerability of vernacular buildings in urban centres: the case of Vila Real de Santo António - Ortega Heras, Javier (2015)
Following detailed studies of Portuguese vernacular building typologies, this paper deals with buildings located in historical urban centres. An analysis of the history of the urban centre and, in particular, of some vernacular buildings is enhanced. Additionally, a discussion on the influence of changes of the geometry, and on added built volumes to original buildings in the seismic vulnerability of the buildings is also provided.